2000
DOI: 10.4049/jimmunol.165.10.5962
|View full text |Cite
|
Sign up to set email alerts
|

Leflunomide Suppresses TNF-Induced Cellular Responses: Effects on NF-κB, Activator Protein-1, c-Jun N-Terminal Protein Kinase, and Apoptosis

Abstract: Leflunomide is a pyrimidine biosynthesis inhibitor that has recently been approved for treatment of rheumatoid arthritis. However, the mechanism of leflunomide’s antiarthritis activity and is not fully understood. The critical role that TNF plays in rheumatoid arthritis led us to postulate that leflunomide blocks TNF signaling. Previously, we have demonstrated that leflunomide inhibits TNF-induced NF-κB activation by suppressing I-κBα (inhibitory subunit of NF-κB) degradation. We in this study show that leflun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(119 citation statements)
references
References 59 publications
5
110
1
3
Order By: Relevance
“…Furthermore, TNF-a can promote angiogenesis, an essential process for tumorigenesis, by inducing the production of angiogenic factors, such as vascular endothelial growth factor and hepatocyte growth factor (Tamura et al, 1993;Yoshida et al, 1997). The production of TNF-a was regulated at several steps and the first one was at the transcription level, governed by transcription factors, such as NF-kB and Activator protein-1AP-1 (Manna et al, 2000;Udalova and Kwiatkowski, 2001;Chung et al, 2007). As Pim-1 can enhance NF-kB transcriptional activity (Zemskova et al, 2008), Pim-3 might be able to similarly activate NF-kB, thereby inducing TNFa expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TNF-a can promote angiogenesis, an essential process for tumorigenesis, by inducing the production of angiogenic factors, such as vascular endothelial growth factor and hepatocyte growth factor (Tamura et al, 1993;Yoshida et al, 1997). The production of TNF-a was regulated at several steps and the first one was at the transcription level, governed by transcription factors, such as NF-kB and Activator protein-1AP-1 (Manna et al, 2000;Udalova and Kwiatkowski, 2001;Chung et al, 2007). As Pim-1 can enhance NF-kB transcriptional activity (Zemskova et al, 2008), Pim-3 might be able to similarly activate NF-kB, thereby inducing TNFa expression.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Shimada et al reported that maximal NF-κB activity was observed at 30 min and sustained for 2 h in human umbilical vein endothelial cells (HUVECs) after treatment with lysophosphatidic acid, a proinflammatory lysophospholipid, but the expression VCAM-1 and ICAM-1 was delayed, peaking at 4 h and remaining for up to 8 h post-drug treatment [39] . In another report, Manna et al observed that NF-κB activation induced by tumor necrosis factor (TNF) can be observed 15 min after stimulation, whereas the earliest time reactive oxygen intermediate (ROI) generation was observed was 1 h poststimulation [40] . Our study also showed that geniposide had the same inhibition ratio of high glucose-induced NF-κB activation and VCAM-1 expression as the NF-κB inhibitor BAY 11-7082.…”
Section: Discussionmentioning
confidence: 99%
“…The HUVECs were seeded at a density of 5×10 3 cells/well in 96-well plates and cultured for 24 h. Then the cells were treated with or without various concentrations of geniposide (1,5,10,20,40 and 80 μg/mL). After 24 h, cell viability was measured using the Cell Counting Kit-8.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…26 The whole-cell extracts were prepared by lysing resveratroltreated cells in lysis buffer (20 mM Tris [pH 7.4], 250 mM NaCl, 2 mM EDTA [pH 8.0], 0.1% Triton X-100, 0.01 mg/mL aprotinin, 0.005 mg/mL leupeptin, 0.4 mM phenylmethylsulphonylfluoride, and 4 mM sodium orthovanadate). After electrophoresis, the proteins were electrotransferred to a nitrocellulose membrane, blocked with 5% nonfat milk, and probed with various antibodies overnight at 4°C.…”
Section: Western Blottingmentioning
confidence: 99%